Genetic diversity of Klebsiella pneumoniae isolates during an outbreak in a non‐human primate research colony. Issue 6 (1st August 2016) - Gozalo, Alfonso S.; Elkins, William R.; Lambert, Lynn E.; Stock, Frida; Thomas, Marvin L.; Woodward, Ruth A.
Abstract: Background: Klebsiella pneumoniae can be a serious pathogen in non‐human primates, particularly Neotropical monkeys. Methods: During a K. pneumoniae outbreak in an owl monkey research colony, 13 K. pneumoniae isolates were DNA fingerprinted by automated repetitive extragenic palindromic‐polymerase chain reaction and the profiles compared to isolates obtained from other non‐human primate species during the same time period and isolates from previous outbreaks. Results: Eleven different types of K. pneumoniae were circulating in the owl monkey colony at the time of the outbreak. When comparing owl monkey isolates relatedness to previous colony outbreak isolates and squirrel monkey and capuchin monkey isolates, all were different. Conclusions: These results agree with recent reports where K. pneumoniae nosocomial isolates in hospital settings can have high genetic diversity, and multiple strains can be circulating simultaneously. This potential genetic diversity should be considered when designing strategies for controlling K. pneumoniae outbreaks in captive non‐human primate colonies.